Pola Kolaborasi dalam Pengamanan Pilkada - Kusumo, Adinda Siti Rosalia; Ma’ruf, Muhammad Farid (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study is motivated by the importance of creating a conducive situation during the 2024 Simultaneous Regional Elections (Pilkada) in Sampang Regency, a region with complex socio-political dynamics. Collaborative efforts among security actors are essential in maintaining stability throughout the election stages. This study aims to analyze the collaboration process between key stakeholders such as the Police (Polres), Military (Kodim 0828), community organizations, media, and the public. The research uses a qualitative case study approach with data collected through in-depth interviews, observation, and documentation. Data were analyzed thematically based on Ansell and Gash’s (2008) Collaborative Governance framework. The findings show that under the starting conditions indicator, collaboration began with resource imbalances between state and non-state actors, mitigated by existing social capital, particularly the roles of NU and local media. In face-to-face dialogue, formal meetings were frequent, but substantial involvement of non-state actors remained limited. Commitment to process was evident through attendance in forums, though equal contributions were lacking. Shared understanding was built around common security goals, yet technical alignment was weak. Facilitative leadership was exercised by KPU and Bawaslu, supporting community initiatives but lacking grassroots outreach. The institutional design remained weak due to the absence of a permanent collaborative forum and reliance on informal coordination. Under outcomes, the election proceeded peacefully, public participation increased, and media effectively countered misinformation, although critical political awareness remained low. The main finding indicates that cross-sector collaboration was constructive but not yet institutionalized. The study recommends establishing a permanent, regulation-based collaboration forum and enhancing participatory political education in the community.